STRATEGI PERIKLANAN, BRANDING, DAN KUALITAS PELAYANAN DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF PKBM TUNAS MEKAR SEMARANG - Lie Fanuel Christanto; Sulartopo Sulartopo; Siti Kholifah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The non-formal education sector, particularly Community Learning Centers (PKBM), faces intensifying competition in maintaining market relevance within the alternative education landscape. This study aims to investigate the influence of Advertising Strategy, Branding, and Service Quality on the Competitive Advantage of PKBM Tunas Mekar Semarang. Adopting a quantitative research design, primary data were collected through Likert-scale questionnaires distributed to the target population. The study utilized a census (saturated) sampling technique, encompassing all 100 active students currently enrolled at PKBM Tunas Mekar Semarang. Data analysis was performed using multiple linear regression analysis via SPSS version 22. The findings demonstrate that Advertising Strategy, Branding, and Service Quality simultaneously exert a significant impact on Competitive Advantage (F-test sig. 0.000 < 0.05). Furthermore, partial analysis (t test) reveals that all three variables have a positive and significant effect: Advertising Strategy (sig. 0.012), Branding (sig. 0.000), and Service Quality (sig. 0.000). The Adjusted R Square value indicates that these factors account for 70.2% of the variance in the institution’s competitive advantage. These results underscore the critical importance of integrating robust marketing strategies with high service standards to strengthen the strategic positioning of non-formal educational institutions in the digital era.